A Gendered Analysis of Individual-Level Asset Poverty in Ecuador. Issue 1 (2nd January 2022) - Anglade, Boaz; Useche, Pilar; Deere, Carmen Diana
Abstract : This study uses individual-level wealth data to explore the gender dimensions of asset poverty among the principal adults in Ecuadorean households, the first such study in a developing country. The study departs from conventional practice by analyzing not only sole heads but also partnered men and women heads and show systematic differences by gender, marital status, and household type. Among both sole and partnered heads, women are more likely to be asset poor than men. Further, in contrast to developed countries, asset poverty rates are much higher among partnered men and women than among sole men and women heads, largely because of structural factors that put those in consensual unions at a disadvantage in accumulating assets. The gender gap, however, is much larger among sole heads. In Ecuador, the risk of asset poverty is mainly associated with low levels of education, type of employment, and not having received an inheritance. HIGHLIGHTS This study uses individual-level asset data to explore the extent of asset poverty in Ecuador. Women in Ecuador are more likely to be asset poor compared to men. The gender asset gap is more prominent among sole heads of household. Asset poverty rates are the highest among women in consensual unions. Education, employment, and inheritance significantly explain asset poverty.